MEMBENTUK AKHLAK MULIA MELALUI PROBLEM BASED LEARNING: STUDI KASUS PEMBELAJARAN AKIDAH AKHLAK DI MADRASAH TSANAWIYAH - Anisa Ashfa Durrotun Nabila; Muhammad Hasyim (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to provide an in-depth description of the effectiveness, challenges and implications of implementing the Problem-Based Learning (PBL) model in fostering students’ moral character in the Akidah Akhlak subject at MTs Sultan Agung, Kalipare. Using a qualitative approach with a case study design, data were collected through in-depth interviews lasting 1 hour and 20 minutes on Wednesday, 4 June 2026. Three key informants were directly involved: Mrs Rosyidah, S.Pdi. (Akidah Akhlak teacher), Mrs Dewi Farizah, S.Pd. (Headteacher), and Mr Ahmad Saji, S.Pd. (Al-Qur’an Hadith teacher). The research findings indicate that the PBL model proved effective in enhancing students’ conceptual understanding and the internalisation of moral values through contextual case studies. Problem-based learning was able to stimulate critical thinking skills, social empathy, and the integration of religious moderation into everyday behaviour. Nevertheless, there were substantial constraints in the form of limited time allocated for classroom preparation and disparities in students’ readiness to engage in formal critical analysis. This study recommends the need for continuous training for educators in designing varied problem scenarios (problem sheets) as well as the need for cross-curricular synergy in strengthening noble character.